Catalyst for producing unsaturated carboxylic acid and method for producing unsaturated carboxylic acid

By optimizing the composition and structure of the catalyst, especially controlling the specific peak width in the X-ray diffraction pattern, the problem of insufficient catalytic activity in the prior art is solved, and efficient production of unsaturated hydroxy acids and long-term stability of the catalyst are achieved.

JP7667381B1Active Publication Date: 2025-04-22NIPPON KAYAKU CO LTD
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
JP2024566613
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2023-09-15
Filing Date
2024-08-21
Publication Date
2025-04-22
Estimated Expiration
2044-08-21

AI Technical Summary

Technical Problem

The prior art produces unsaturated hydroxy acids, which lacks catalytic activity, resulting in low yield, short catalyst life, and poor pyrolysis, affecting long-term stable operation.

Method used

Catalytic activity is improved by optimizing the composition and structure of the catalyst, especially controlling the specific peak width in the X-ray diffraction pattern. The specific method includes using a specific proportion of molybdenum, vanadium, tungsten, copper, antimony and other elements, and adjusting through spray drying and pre-firing processes to control the crystal structure and surface characteristics of the catalyst.

Benefits of technology

In the gas-phase catalytic oxidation reaction, the yield of unsaturated hydroxy acids and the long-term stability of the catalyst are achieved, energy consumption and pyrolysis problems are reduced, and efficient and long-lasting catalytic performance is ensured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007667381000004
    Figure 0007667381000004
  • Figure 0007667381000001
    Figure 0007667381000001
  • Figure 0007667381000002
    Figure 0007667381000002
Patent Text Reader

Abstract

The present disclosure relates to a catalyst for producing an unsaturated carboxylic acid, the catalytically active component of which has a composition represented by the following formula (1), and the half-width of the peak at 22.2°±0.3° in an X-ray diffraction pattern obtained using CuKα radiation as an X-ray source is 0.65° or more and 1.60° or less. (Mo) 12 (V) a (W) b (Cu) c (Sb) d (X) e (Y) f (Z) g (O) h (1)
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a catalyst for producing an unsaturated carboxylic acid in high yield by vapor-phase catalytic oxidation of an unsaturated aldehyde in the presence of molecular oxygen or a molecular oxygen-containing gas, a method for producing the same, and a method for producing an unsaturated carboxylic acid using the catalyst. [Background technology]

[0002] Acrylic acid is becoming increasingly important as a raw material for water-absorbent resins, adhesives, etc. Therefore, in recent years, there has been a demand for improved catalyst performance for producing acrylic acid by gas-phase catalytic oxidation reaction using acrolein as a raw material. Therefore, various companies have been making various improvements to catalysts that can produce acrylic acid stably in high yield for a long period of time, and for example, the following proposals have been made.

[0003] Patent Documents 1 to 4 disclose improvements in catalyst composition, etc., focusing on the X-ray diffraction peaks of catalytically active components. These catalysts have been proposed as catalysts that achieve high activity and high yield. Patent Documents 5 and 6 also provide improvement guidelines aimed at improving mechanical strength, and improve catalyst performance through prevention of powdering during filling. Patent Document 7 aims to improve the long-term stability of catalytic reactions by setting the standard deviation of catalyst particle size within a specific range. Patent Document 8 proposes a method for producing a catalyst that combines high catalytic performance and mechanical strength by controlling the relative centrifugal acceleration when molding using a rolling granulator. Patent Document 9 proposes a method for producing a high-yield catalyst by controlling the density of the catalyst molded body and the roughness of the catalyst surface. Patent Document 10 proposes a production method for obtaining high activity and selectivity by controlling the crystal size within a specific range in nanocrystalline molybdenum mixed oxide.

[0004] However, especially in the production of unsaturated carboxylic acids, improving catalytic activity is an important issue. This not only contributes to improving the yield, but is also important from the viewpoint of catalyst life. For example, in a plant using a catalyst, if the reaction bath temperature at the beginning of the reaction is reduced by improving the catalytic activity, not only will the energy cost for heating be reduced, but the thermal deterioration of the catalyst will also be reduced, so that there will be less performance degradation from a long-term perspective, and stable operation and high yields can be achieved over a long period of time. For these reasons, there is a demand for highly active catalysts and methods for producing the same. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Japanese Patent Publication No. 8-299797 [Patent Document 2] Japanese Patent Publication No. 2003-251184 [Patent Document 3] Japanese Patent Publication No. 2015-120133 [Patent Document 4] Japanese Patent Application Publication No. 2018-43197 [Patent Document 5] Japanese Patent Publication No. 2001-79408 [Patent Document 6] International Publication No. 2012 / 073584 [Patent Document 7] Japanese Patent Publication No. 2009-214105 [Patent Document 8] Japanese Patent Application Publication No. 2015-96497 [Patent Document 9] International Publication No. 2020 / 196150 [Patent Document 10] Japan Special Publication No. 2011-516378 Summary of the Invention [Problem to be solved by the invention]

[0006] In view of the above circumstances, an object of the present invention is to improve the catalytic activity of a catalyst for producing an unsaturated carboxylic acid from an unsaturated aldehyde as a raw material by a gas-phase catalytic oxidation reaction. [Means for solving the problem]

[0007] As a result of extensive research into the current situation and problems described above, the inventors of the present application have found that certain parameters in the X-ray diffraction pattern contribute to improving activity, and have thus made the present invention.

[0008] That is, the present invention relates to the following 1) to 6). 1) A catalyst for producing an unsaturated carboxylic acid, comprising a catalytically active component having a composition represented by the following formula (1), and an X-ray diffraction pattern obtained using CuKα radiation as an X-ray source, in which the half-width of a peak at 22.2°±0.3° is 0.65° or more and 1.60° or less: (Mo) 12 (V) a (W) b (Cu) c (Sb) d (X) e (Y) f (Z) g (O) h (1) (In formula (1), Mo, V, W, Cu, Sb, and O represent molybdenum, vanadium, tungsten, copper, antimony, and oxygen, respectively; X represents at least one element selected from the group consisting of alkali metals and thallium; Y represents at least one element selected from the group consisting of magnesium, calcium, strontium, barium, and zinc; Z represents at least one element selected from the group consisting of niobium, cerium, tin, chromium, manganese, iron, cobalt, samarium, germanium, titanium, and arsenic. Also, a, b, c, d, e, f, g, and h represent the atomic ratios of the respective elements. With respect to 12 molybdenum atoms, 0 < a ≤ 10.0, 0 ≤ b ≤ 10.0, 0 < c ≤ 6.0, 0 ≤ d ≤ 10.0, 0 ≤ e ≤ 0.50, 0 ≤ f ≤ 1.0, 0 ≤ g < 6.0. Further, h is the number of oxygen atoms necessary to satisfy the valences of the respective components.) 2) The catalyst for producing an unsaturated carboxylic acid according to 1) above, wherein in the above formula (1), 1.0 ≤ a ≤ 5.0, 0.50 ≤ b ≤ 3.0, 0.50 ≤ c ≤ 3.0, and 0 < d ≤ 2.0. 3) The catalyst for producing an unsaturated carboxylic acid according to 1) or 2) above, which is a catalyst in which a catalytically active component is supported on an inert carrier. 4) The catalyst for producing an unsaturated carboxylic acid according to 3) above, wherein the inert carrier is silica, alumina, or a combination thereof. 5) A method for producing an unsaturated carboxylic acid using the catalyst for producing an unsaturated carboxylic acid according to any one of 1) to 4) above. 6) A method for producing an unsaturated carboxylic acid using a reaction tube filled with two or more kinds of the catalysts for producing an unsaturated carboxylic acid according to any one of 1) to 4) above in multiple layers.

Advantages of the Invention

[0009] According to the present invention, when producing an unsaturated carboxylic acid, namely (meth)acrylic acid, by subjecting an unsaturated aldehyde, preferably (meth)acrolein, to a gas-phase catalytic oxidation reaction as a raw material, the catalytic activity can be maintained at a high level. [Brief description of the drawings]

[0010] [Figure 1] FIG. 2 is an XRD chart of the catalytically active component of the catalyst 1 produced in Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] [FWHM of peak at 22.2°±0.3°] The catalyst of the present invention has an X-ray diffraction (XRD) pattern obtained using CuKα radiation as an X-ray source, in which the half-width of the peak at 22.2°±0.3° is 0.65° or more and 1.60° or less. In this specification, the half width means the full width at half maximum, that is, the width at the part where the intensity is 1 / 2 of the peak value as a quadratic function after fitting described later. Although the details of how the half width of the peak at 22.2°±0.3° in the X-ray diffraction pattern affects the activity are unclear, since there is a clear correlation between the half width of the peak at 22.2°±0.3° and the catalytic activity, it is believed that a specific crystal structure causes the oxidation reaction of (meth)acrolein. Most of the active components of the catalyst for producing (meth)acrylic acid of the present invention have an amorphous structure, but it is believed that the partially existing crystals show high catalytic activity. The half-width of the peak at 22.2°±0.3° in the X-ray diffraction pattern becomes smaller when the crystals having a diffraction plane at 22.2°±0.3° grow. The oxidation reaction of (meth)acrolein is believed to proceed inside the crystal structure, and the more the crystals grow, the more reaction sites there are inside the crystal structure, which is believed to improve the activity of the catalyst. However, if the crystals become too large, physical resistance occurs, making it difficult for the raw material (meth)acrolein to pass through the inside of the crystal structure, which is believed to reduce the activity. In addition, the half-width of the peak at 22.2°±0.3° also increases or decreases depending on the number of crystals. When the proportion of amorphous parts in the active ingredient decreases and the number of crystals increases, the diffraction plane increases, so the half-width decreases, and the activity improves because the amount of highly active ingredients increases. In addition, the half-width of the peak at 22.2°±0.3° also increases or decreases depending on the distortion of the crystal structure. It is generally believed that catalytic reactions are more likely to proceed in areas with structural defects, and it is believed that catalysts for the production of (meth)acrylic acid also have a higher activity when there is a certain degree of structural defect. When there is a structural defect, the crystal structure is distorted, and the half-width of the peak at 22.2°±0.3° in the X-ray diffraction pattern becomes a large value. Generally speaking, the inventors of the present invention believe that a catalyst in which the degree of crystal growth and structural distortion are within a certain range and the number of crystals is large is a preferable form for a catalyst for producing (meth)acrylic acid, and have found that this can be achieved by adjusting the half-width of the peak at 22.2°±0.3° in the X-ray diffraction pattern to be 0.65° or more and 1.60° or less.

[0012] The half width in the present invention is 0.65° or more and 1.60° or less, and more preferably the lower limit is 0.70°, 0.75°, 0.80°, 0.85°, 0.88°, 0.90°, 0.92°, 0.94°, 0.96°, and particularly preferably 0.98°. Similarly, the upper limit is preferably 1.55°, 1.50°, 1.47°, 1.45°, 1.40°, 1.35°, 1.33°, and particularly preferably 1.31°. Therefore, the half-width of the peak at 22.2°±0.3° is preferably 0.70° or more and 1.60° or less, more preferably 0.75° or more and 1.60° or less, more preferably 0.80° or more and 1.60° or less, more preferably 0.85° or more and 1.55° or less, more preferably 0.88° or more and 1.50° or less, more preferably 0.90° or more and 1.47° or less, more preferably 0.92° or more and 1.45° or less, more preferably 0.94° or more and 1.40° or less, more preferably 0.96° or more and 1.35° or less, and most preferably 0.98° or more and 1.31° or less. The half-width of the peak at 22.2°±0.3° may be 0.65° or more and 1.47° or less, 0.65° or more and 1.45° or less, 0.65° or more and 1.40° or less, 0.85° or more and 1.60° or less, 0.88° or more and 1.60° or less, or 0.90° or more and 1.60° or less.

[0013] A method for measuring the X-ray diffraction angle (2θ) may be, for example, to use an Ultima IV manufactured by Rigaku Corporation, and to measure the X-ray diffraction angle (2θ) under the conditions of X-ray CuKα radiation (λ=0.154 nm), output of 40 kV, 30 mA, measurement range of 5 to 60°, and measurement speed of 3° per minute; however, the method is not limited to these as long as it does not deviate from the measurement principle.

[0014] [Calculation method for half-width of peak at 22.2°±0.3°] In calculating the half-width, it is recommended to use data that has not been processed, such as by smoothing the baseline, and to use OriginPro manufactured by LightStone as the analysis software. The analysis method is to use the straight line passing through the minimum value of 2θ=16.0°-18.0° and the minimum value of 2θ=39.0°-42.0° in the X-ray diffraction pattern as the baseline, fit a quadratic function to the peaks above the baseline, and read the full width at half maximum of the fitted quadratic function with a peak in the range of 2θ=22.2°±0.3° as the half-width of the peak at 2θ=22.2°±0.3° in the X-ray diffraction pattern.

[0015] [FWHM of peak at 8.3°±0.5°] From the viewpoint of catalytic activity, the catalyst of the present invention is more preferably one in which the half-width of the peak at 8.3°±0.5° is greater than 0 and not greater than 2.82°. The upper limit of the half-width of the peak at 8.3°±0.5° is more preferably 2.75°, 2.70°, 2.65°, 2.60°, 2.55°, 2.50°, 2.45°, 2.40°, and particularly preferably 2.37°. Similarly, the lower limit is more preferably 1.00°, 1.50°, 2.00°, 2.10°, 2.20°, and particularly preferably 2.30°. Therefore, the half-width of the peak at 8.3°±0.5° is more preferably greater than 0 and not greater than 2.75°, more preferably greater than 0 and not greater than 2.70°, more preferably greater than 0 and not greater than 2.65°, more preferably 1.00° or more and not greater than 2.60°, more preferably 1.50° or more and not greater than 2.55°, more preferably 2.00° or more and not greater than 2.50°, more preferably 2.10° or more and not greater than 2.45°, more preferably 2.20° or more and not greater than 2.40°, and most preferably 2.30° or more and not greater than 2.37°.

[0016] [Calculation method for half-width of peak at 8.3°±0.5°] The method for calculating the half-width of the peak at 22.2°±0.3° is the same as that for calculating the half-width of the peak at 22.2°±0.3°, except that the half-width of the quadratic function after fitting that has a peak in the range of 2θ=8.3°±0.5° is read as the half-width of the peak.

[0017] [FWHM of peak at 26.7°±0.3°] From the viewpoint of catalytic activity, the catalyst of the present invention is more preferably one in which the half-width of the peak at 26.7°±0.3° is 4.66° or more and 7.40° or less. More preferably, the upper limit of the half-width of the peak at 26.7°±0.3° is 7.30°, 7.25°, 7.20°, 7.00°, 6.90°, 6.80°, 6.70°, 6.60°, 6.50°, 6.40°, 6.30°, 6.20°, 6.15°, or 6.10°, and particularly preferably 6.05°. Similarly, the lower limit is more preferably 4.80°, 5.00°, 5.05°, 5.10°, 5.20°, 5.30°, 5.40°, 5.45°, 5.50°, 5.60°, 5.70°, 5.80°, or 5.90°, and is particularly preferably 5.95°. Therefore, the half width of the peak at 26.7°±0.3° is more preferably 4.66° or more and 7.30° or less, more preferably 4.66° or more and 7.25° or less, more preferably 4.80° or more and 7.20° or less, more preferably 5.00° or more and 7.00° or less, more preferably 5.10° or more and 6.90° or less, more preferably 5.20° or more and 6.80° or less, more preferably 5.30° or more and 6.70° or less, more preferably 5.40° or more and 6.60° or less, more preferably 5.45° or more and 6.50° or less, more preferably 5.50° or more and 6.40° or less, more preferably 5.60° or more and 6.30° or less, more preferably 5.70° or more and 6.20° or less, more preferably 5.80° or more and 6.15° or less, more preferably 5.90° or more and 6.10° or less, and most preferably 5.95° or more and 6.05° or less.

[0018] [Calculation method for half-width of peak at 26.7°±0.3°] The method for calculating the half-width of the peak at 22.2°±0.3° is the same as that for calculating the half-width of the peak at 22.2°±0.3°, except that the half-width of the quadratic function having a vertex in the range of 2θ=26.7°±0.3° after fitting is read as the half-width of the peak.

[0019] [FWHM of peak at 45.4°±0.3°] From the viewpoint of catalytic activity, the catalyst of the present invention is more preferably one in which the half-width of the peak at 45.4°±0.3° is 0.64° or more and 1.03° or less. More preferably, the upper limit of the half-width of the peak at 45.4°±0.3° is 1.00°, 0.99, 0.98°, and particularly preferably 0.97°. Similarly, more preferably, the lower limit is 0.65°, 0.67°, 0.70°, 0.75°, 0.80°, 0.85°, and 0.90°, and particularly preferably 0.95°. Therefore, the half-width of the peak at 45.4°±0.3° is more preferably 0.65° or more and 1.03° or less, more preferably 0.67° or more and 1.03° or less, more preferably 0.70° or more and 1.03° or less, more preferably 0.75° or more and 1.03° or less, more preferably 0.80° or more and 1.00° or less, more preferably 0.85° or more and 0.99° or less, more preferably 0.90° or more and 0.98° or less, and most preferably 0.95° or more and 0.97° or less.

[0020] [Calculation method for half-width of peak at 45.4°±0.3°] The method for calculating the half-width of the peak at 22.2°±0.3° is the same as that for calculating the half-width of the peak at 22.2°±0.3°, except that the half-width of the quadratic function after fitting, which has a peak in the range of 2θ=45.4°±0.3°, is read as the half-width of the peak.

[0021] [Catalyst composition] The catalyst of the present invention has a composition represented by the following formula (1). [Formula (1)] (Mo) 12 (V) a (W) b (Cu) c (Sb) d (X) e (Y) f (Z) g (O) h (1) (In the formula, Mo, V, W, Cu, Sb, and O represent molybdenum, vanadium, tungsten, copper, antimony, and oxygen, respectively; X represents at least one element selected from the group consisting of an alkali metal and thallium; Y represents at least one element selected from the group consisting of magnesium, calcium, strontium, barium, and zinc; Z represents at least one element selected from the group consisting of bismuth, tellurium, silver, selenium, silicon, aluminum, boron, niobium, cerium, tin, chromium, manganese, iron, cobalt, nickel, samarium, germanium, zirconium, titanium, chromium, tantalum, lead, indium, sulfur, palladium, gallium, lanthanum, and arsenic. Also, a, b, c, d, e, f, g, and h represent the atomic ratios of the respective elements. With respect to 12 molybdenum atoms, 0 < a ≤ 10.0, 0 ≤ b ≤ 10.0, 0 < c ≤ 6.0, 0 ≤ d ≤ 10.0, 0 ≤ e ≤ 0.50, 0 ≤ f ≤ 1.0, 0 ≤ g < 6.0. Also, h is the number of oxygen atoms necessary to satisfy the valences of the respective components.)

[0022] In the above formula (1), the preferred ranges of a to g are as follows. The lower limits of a are, in order of preference, 0.20, 0.50, 0.80, 1.0, 1.5, 2.0, 2.2, 2.4, and most preferably 2.6. The upper limits of a are, in order of preference, 9.0, 8.0, 7.0, 6.0, 5.0, 4.5, 4.0, 3.5, 3.3, 3.1, and most preferably 2.9. That is, as the range of a, 0.20 ≤ a ≤ 9.0 is preferred, 0.20 ≤ a ≤ 8.0 is more preferred, 0.20 ≤ a ≤ 7.0 is more preferred, 0.50 ≤ a ≤ 6.0 is more preferred, 0.80 ≤ a ≤ 5.0 is more preferred, 1.0 ≤ a ≤ 4.5 is more preferred, 1.5 ≤ a ≤ 4.0 is more preferred, 2.0 ≤ a ≤ 3.5 is more preferred, 2.2 ≤ a ≤ 3.3 is more preferred, 2.4 ≤ a ≤ 3.1 is more preferred, and most preferably, 2.6 ≤ a ≤ 2.9. The lower limit of b is, in order of desirability, 0.10, 0.20, 0.30, 0.40, 0.50, and 0.60, and is most desirably 0.70, and the upper limit of b is, in order of desirability, 9.0, 8.0, 7.0, 6.0, 5.0, 4.0, 3.0, 2.5, 2.0, 1.5, and 1.3, and is most desirably 1.1. That is, the range of b is preferably 0.10≦b≦9.0, more preferably 0.10≦b≦8.0, more preferably 0.10≦b≦7.0, more preferably 0.10≦b≦6.0, more preferably 0.10≦b≦5.0, more preferably 0.10≦b≦4.0, more preferably 0.20≦b≦3.0, more preferably 0.30≦b≦2.5, more preferably 0.40≦b≦2.0, more preferably 0.50≦b≦1.5, more preferably 0.60≦b≦1.3, and most preferably 0.70≦b≦1.1. The lower limit of c is, in order of desirability, 0.10, 0.20, 0.30, 0.40, 0.50, 0.60, 0.70, 0.80, 0.90, and 1.0, and is most desirably 1.3, and the upper limit of c is, in order of desirability, 5.0, 4.0, 3.0, 2.5, 2.0, and 1.8, and is most desirably 1.6. That is, the range of c is preferably 0.10≦c≦5.0, more preferably 0.20≦c≦5.0, more preferably 0.30≦c≦5.0, more preferably 0.40≦c≦5.0, more preferably 0.50≦c≦5.0, more preferably 0.60≦c≦4.0, more preferably 0.70≦c≦3.0, more preferably 0.80≦c≦2.5, more preferably 0.90≦c≦2.0, more preferably 1.0≦c≦1.8, and most preferably 1.3≦c≦1.6. The lower limit of d is, in order of desirability, 0.11, 0.15, 0.18, 0.20, 0.25, 0.30, and 0.35, and is most desirably 0.40, and the upper limit of d is, in order of desirability, 9.0, 8.0, 7.0, 6.0, 5.0, 4.0, 3.0, 2.5, 2.0, 1.5, and 1.0, and is most desirably 0.70. That is, the range of d is preferably 0.11≦d≦9.0, more preferably 0.11≦d≦8.0, more preferably 0.11≦d≦7.0, more preferably 0.11≦d≦6.0, more preferably 0.11≦d≦5.0, more preferably 0.15≦d≦4.0, more preferably 0.18≦d≦3.0, more preferably 0.20≦d≦2.5, more preferably 0.25≦d≦2.0, more preferably 0.30≦d≦1.5, more preferably 0.35≦d≦1.0, and most preferably 0.40≦d≦0.70. The upper limit of e is, in order of desirability, 0.40, 0.30, 0.20, and 0.10. That is, the range of e is, in order of desirability, 0≦e≦0.40, 0≦e≦0.30, and 0≦e≦0.20, and the most preferable range is 0≦e≦0.10. The upper limit of f is, in order of preference, 0.80, 0.50, 0.20, and 0.15, and is most preferably 0.10. That is, the range of f is, in order of preference, 0≦f≦0.80, 0≦f≦0.50, 0≦f≦0.20, and 0≦f≦0.15, and the most preferable range is 0≦f≦0.10. The upper limit of g is, in order of desirability, 5.0, 4.0, 3.0, 2.0, and 1.0. That is, the range of g is, in order of desirability, 0≦g≦5.0, 0≦g≦4.0, 0≦g≦3.0, and 0≦g≦2.0, and the most preferable range is 0≦g≦1.0. In a particularly preferred embodiment, e, f and g are 0.

[0023] When the catalyst of the present invention is used in a reaction for producing a corresponding unsaturated carboxylic acid from an unsaturated aldehyde such as acrolein or methacrolein as a raw material, particularly in a reaction for producing acrylic acid by gas-phase catalytic oxidation of acrolein with molecular oxygen or a molecular oxygen-containing gas, it is very effective in improving catalytic activity and reducing the differential pressure compared to known methods. In addition, in a process of partial oxidation reaction accompanied by heat generation, it is expected to improve stability by reducing hot spot temperature, etc. Furthermore, the catalyst of the present invention is also effective in reducing by-products that adversely affect the environment and the quality of the final product, such as carbon monoxide (CO), carbon dioxide (CO2), acetaldehyde, acetic acid, and formaldehyde.

[0024] [Catalyst manufacturing method, etc.] A specific example of the process for obtaining the catalyst of the present invention will be described below. Step a) Mixing Examples of raw materials for the elements constituting the catalyst include those shown below. When ammonium molybdate is used as the molybdenum component raw material, a high performance catalyst is obtained. As the raw materials of tungsten, vanadium, antimony, copper and other elements, ammonium salts, carbonates, sulfates, organic acid salts, hydroxides, metal powders, etc., which can be oxides or oxides by ignition, or mixtures thereof can be used. The preferred raw materials vary depending on the type of element, and the half-width of the peak at 22.2°±0.3° in the XRD pattern can also be adjusted accordingly. For example, ammonium salts are preferred for tungsten and vanadium, and sulfates are preferred for copper. In the case of antimony raw materials, compounds in which the valence of antimony is trivalent are preferred, and acetic acid, carbonic acid, tartaric acid, oxalic acid, and other carboxylic acid salts are particularly preferred. The vanadium raw material, molybdenum raw material, tungsten raw material, and antimony raw material are mixed in a desired ratio in an aqueous solvent at 20 to 95°C, heated and stirred for about 1 hour, and then X component raw material, Y component raw material, and Z component raw material are added as necessary, and finally an aqueous solution in which the copper raw material is dissolved is added. An aqueous solution or slurry containing the catalyst components is obtained, which is hereinafter referred to as the prepared liquid (A). When using metal powder as a raw material, it is preferable to add it at the same time as the antimony raw material, and when using a divalent copper raw material as the copper raw material, it is preferable to add it after the antimony raw material and metal powder are added. If the divalent copper raw material is added before the antimony raw material and metal powder, low activity crystals are generated, leading to a decrease in catalyst performance. Here, the preparation liquid (A) does not necessarily contain all the catalyst constituent elements, and some of the elements or some of the amounts may be added in a subsequent step. In addition, when preparing the preparation liquid (A), if the amount of water in which each component raw material is dissolved or an acid such as sulfuric acid, nitric acid, hydrochloric acid, tartaric acid, or acetic acid is added for dissolution, the acid concentration in the aqueous solution sufficient to dissolve the raw materials is not appropriate, for example, within the range of 5% by mass to 99% by mass, the preparation liquid (A) may take the form of a clay-like mass, which will not be an excellent catalyst. Therefore, it is preferable that the preparation liquid (A) obtained is in the form of an aqueous solution or a slurry, in order to obtain an excellent catalyst.

[0025] Step b) Drying Next, the prepared liquid (A) obtained above is dried to obtain a dry powder. The drying method is not particularly limited as long as it can completely dry the prepared liquid (A), and examples thereof include drum drying, freeze drying, spray drying, and evaporation to dryness. Among these, in the present invention, spray drying is particularly preferred, which can dry the slurry into powder or granules in a short time. The drying temperature of the spray drying varies depending on the concentration of the slurry, the liquid sending speed, etc., but is generally 70 to 150°C at the outlet of the dryer. In addition, it is preferable to dry the mixture so that the average particle size of the dry powder obtained at this time is 20 to 700 μm. In this way, a dry powder (B) is obtained.

[0026] Step c) Pre-firing The resulting dry powder (B) is calcined under air flow at 200°C to 500°C, preferably 300°C to 400°C, which tends to improve the moldability, mechanical strength, and catalytic performance of the catalyst. The calcination time is preferably 1 hour to 12 hours. In this way, a pre-calcined body (C) is obtained.

[0027] Step d) Crushing The obtained pre-fired body (C) is obtained as a solid (D) in which the dry powder (B) is aggregated by pre-firing. In order to obtain the pre-fired powder (E) required for the next molding step, the solid (D) is pulverized. The pulverization method is not particularly limited, and examples thereof include a roller mill, a jet mill, a hammer mill, a ball mill, and a vibration mill. The average particle size (pre-fired median size) of the pre-fired powder (E) obtained at this time is preferably 50 μm or less, more preferably 40 μm or less, even more preferably 30 μm or less, and particularly preferably 25 μm or less. In the present specification, the crushed pre-calcined powder (E) is described as a catalyst precursor. However, in the case where there is no agglomeration at the pre-calcined body (C) stage and it can be used without going through a crushing step, the pre-calcined body (C) may be used as a catalyst precursor.

[0028] Process e) Molding There is no particular limitation on the molding method, but when molding into a cylindrical or ring shape, a method using a tablet molding machine, an extrusion molding machine, etc. is preferred. More preferably, when molding into a spherical shape, the pre-sintered powder (E) may be molded into a spherical shape using a molding machine, but a method in which the pre-sintered powder (E) (containing a molding aid and a strength improver, if necessary) is supported on a carrier such as an inactive ceramic is preferred. Here, the widely known methods of loading include the rolling granulation method, the method using a centrifugal fluidized coating device, the wash coat method, etc., and are not particularly limited as long as the pre-calcined powder (E) can be uniformly loaded on the carrier, but considering the production efficiency of the catalyst and the performance of the catalyst to be prepared, it is more preferable to use a device having a flat or uneven disk at the bottom of a fixed cylindrical container, which is rotated at high speed to vigorously stir the carrier charged in the container by the rotation and revolution of the carrier itself, and the pre-calcined powder (E) and, if necessary, a molding aid and / or a strength improver and a pore former are added to the container to load the powder components on the carrier, and the rolling granulation method is the most preferable. It is preferable to use a binder when loading. Specific examples of binders that can be used include water, ethanol, methanol, propanol, polyhydric alcohols, polyvinyl alcohol as a polymer binder, and silica sol aqueous solution as an inorganic binder. Ethanol, methanol, propanol, and polyhydric alcohols are preferred, and diols such as ethylene glycol and triols such as glycerin are more preferred. By using an appropriate amount of glycerin aqueous solution, moldability is improved and a high-performance catalyst with high mechanical strength can be obtained. Specifically, a particularly high-performance catalyst can be obtained when an aqueous solution of glycerin with a concentration of 5% by mass or more is used. The amount of these binders used is usually 2 to 80 parts by mass per 100 parts by mass of the pre-calcined powder (E). An inert carrier of about 2 to 8 mm is usually used, and the pre-calcined powder (E) is supported on it. The support rate is determined in consideration of the catalyst use conditions, such as the space velocity of the reaction raw materials and the raw material concentration, and is usually 20% by mass to 80% by mass. Here, the support rate is expressed as the following formula (4) when a molding assistant or strength improver is used in molding. In this way, a molded body (F) is obtained. In addition, the present inventors have found that the catalyst of the present invention may have poor mechanical strength. Therefore, it is preferable to add inactive inorganic fibers as a strength improver during the support molding. The amount of these fibers used is usually 1 to 30 parts by mass per 100 parts by mass of the pre-calcined powder (E).

[0029] [About support] A catalyst in which the pre-calcined body (C) obtained by pre-calcining the catalytically active component after its preparation, or the pre-calcined body (C) is further subjected to a pulverization process to obtain the pulverized pre-calcined powder (E) is supported on an inert carrier is particularly effective. The inert carrier may be made of known materials such as alumina, silica, titania, zirconia, niobia, silica alumina, silicon carbide, carbide, and mixtures thereof. The particle size, water absorption rate, mechanical strength, degree of crystallinity of each crystal phase, and mixture ratio of the inert carrier are not particularly limited, and an appropriate range should be selected in consideration of the final catalyst performance, moldability, production efficiency, etc. The shape of the inert carrier is preferably spherical, but is not particularly limited, and pellets or rings are used. The mixture ratio of the carrier and the pre-calcined powder is generally calculated as the loading rate according to the following formula (4) depending on the charged mass of each raw material. In addition, if it is clear that additives such as molding aids and strength improvers remain in the catalyst after the main calcination, they are included in the total amount (denominator). [Formula (4)] Loading rate (mass%) = (mass of pre-calcined powder used for molding) / {(mass of pre-calcined powder used for molding) + (mass of support used for molding)} × 100 (4) The preferred upper limit of the above-mentioned loading rate is 80% by mass, and more preferred rates are 70, 60, 55, 50, 45 and 40% by mass. The lower limit is preferably 10% by mass, and more preferably 15, 18, and 20% by mass. That is, the loading rate is preferably 10% by mass or more and 80% by mass or less, more preferably 10% by mass or more and 70% by mass or less, more preferably 10% by mass or more and 60% by mass or less, more preferably 10% by mass or more and 55% by mass or less, more preferably 15% by mass or more and 50% by mass or less, more preferably 18% by mass or more and 45% by mass or less, and the most preferable range is 20% by mass or more and 40% by mass or less.

[0030] [About inorganic fibers] The catalyst of the present invention preferably contains inorganic fibers for the purpose of improving mechanical strength, etc. The material of the inorganic fibers is not particularly limited, and for example, glass fibers (glass fibers), ceramic fibers, metal fibers, mineral fibers, carbon fibers, various whiskers, etc. can be used. Among these, glass fibers treated with silane-based chemicals are particularly preferred. The fiber length is not particularly limited as long as it does not impair the effects of the present invention, but the average fiber length is preferably about 1 to 1000 μm, more preferably about 10 to 500 μm. Furthermore, two or more kinds of inorganic fibers can be used in combination. Two or more kinds of fibers may be made of different materials, or two kinds of fibers made of the same material but with different average fiber lengths.

[0031] Step f) Main firing The catalytic activity and effective yield of the molded body (F) tend to improve when it is calcined at a temperature of 100 to 450°C for about 1 to 12 hours. The calcination temperature is preferably 270°C or higher and 420°C or lower, and more preferably 350°C or higher and 400°C or lower. Air is the preferred gas to be circulated because it is simple, but other inert gases such as nitrogen, carbon dioxide, argon, helium, nitrogen oxide-containing gas for creating a reducing atmosphere, ammonia-containing gas, hydrogen gas, and mixtures thereof can also be used. In this way, the catalyst (G) is obtained.

[0032] [How to adjust the half-width of the peak at 22.2°±0.3°] The value of the above half-width can be adjusted by changing the following: the type of raw material used in step a), the spray-drying conditions in step b), the firing temperature, time, and atmosphere in step c), the grinding method and the median diameter after grinding in step d), the relative centrifugal acceleration, the loading rate, the type of binder, the addition position of the binder, etc. in step e). However, it is difficult to significantly change it by changing a single condition alone, and it can be achieved by optimizing two or more conditions. Several examples are shown below.

[0033] <Compared with the type of raw material used in step a)> The half-width of the peak at 22.2° ± 0.3° in the XRD pattern can be adjusted by changing the type of raw material used. In particular, it is better to change the compound that can act as a reducing agent. When using a trivalent antimony compound, the half-width becomes larger, and when using metal powders such as molybdenum or copper with an oxidation number of 0, or organic substances such as oxalic acid or citric acid, the half-width becomes smaller. Also, it is possible to control the half-width by adjusting the composition ratio of the metal elements. The catalyst of the present invention has a basic skeleton of molybdenum and vanadium, and as the number of other elements increases, the crystal structure becomes distorted, so the half-width tends to become larger. In particular, tungsten and antimony atoms strongly distort the crystal structure, so the more these raw materials are used, the easier it is for the half-width to become larger. Conversely, the more copper raw material is used, the easier it is for the half-width to become smaller. From this perspective, for example, the atomic ratio d of antimony to 12 molybdenum atoms in formula (1) may be 0 < d < 1.0, may be 0.25 ≦ d ≦ 0.75, or may be 0.25 ≦ d ≦ 0.50.

[0034] <The firing temperature, time, and atmosphere in step c)> As described above, the firing temperature is preferably 200°C to 500°C. When it is increased, crystal growth is promoted, so the half-width tends to become smaller. However, if the temperature is too high or the time is too long, the crystals will thermally decompose and the number will decrease, so the half-width will become larger. Therefore, from the perspective of adjusting the half-width, it is preferably less than 400°C and less than 6 hours. The gas atmosphere during firing may be air, but since the presence of oxygen molecules inhibits crystal growth, firing in an inert gas atmosphere such as nitrogen or argon or in a reducing gas atmosphere such as hydrogen or ammonia can reduce the full width at half maximum (FWHM). <d) Grinding method, median diameter, and centrifugal acceleration in the process> The FWHM can also be controlled by the method of step d), but when using a ball mill, it is easy to adjust the FWHM, and it can also be adjusted by making the median diameter of the pre-fired powder below a certain value. The median diameter of the pre-fired powder is preferably 50 μm or less. Also, depending on the median diameter of the pre-fired powder, the FWHM can be adjusted by changing the relative centrifugal acceleration when the process e) is rolling granulation. When the median diameter is less than 30 μm, the relative centrifugal acceleration is preferably 10 G or more.

[0035] [Use of the catalyst] In the method for producing an unsaturated carboxylic acid such as acrylic acid using the catalyst of the present invention, the flow method of the raw material gas may be a normal single-pass method or a recycle method, and it can be carried out under generally used conditions and is not particularly limited. For example, a mixed gas consisting of 1 to 10% by volume, preferably 4 to 9% by volume, of the starting raw material substance as an ideal gas, 3 to 20% by volume, preferably 4 to 18% by volume, of molecular oxygen, 0 to 60% by volume, preferably 4 to 50% by volume, of water vapor, and 20 to 80% by volume, preferably 30 to 75% by volume, of an inert gas such as carbon dioxide and nitrogen is filled into the reaction tube and introduced onto the catalyst of the present invention at 200 to 450 °C under a pressure of normal pressure to 10 atmospheres, with a space velocity of 300 to 5000 h -1 and the reaction is carried out. In the method for producing unsaturated carboxylic acid, one type of catalyst may be used alone, or different types of catalysts may be used in a multi-layered packing depending on the conditions of use. That is, a method can be adopted in which a catalyst layer formed by dividing into n parts in the raw gas flow direction of a reaction tube is provided, and the above-mentioned multiple types of catalysts are arranged so that their activity becomes higher from the raw material inlet to the outlet in the raw material flow direction. The number of divisions n is not particularly limited, but is usually 2 to 5, preferably 2 to 3. The above-mentioned different types of catalysts do not only mean the case where the catalyst composition is different, but also include the case where the support rate on an inert carrier is different or the case where the dilution rate is different. In addition, a method can be adopted in which a catalyst highly activated by adjusting the half-width of the present invention is arranged on the raw material gas outlet side, and a catalyst with a relatively low activity is arranged on the raw material gas inlet side. EXAMPLES

[0036] The present invention will be described in more detail below with reference to examples. In the examples, the raw material conversion, yield and selectivity were calculated according to the following formulas. Raw material conversion rate (%) = (number of moles of reacted acrolein) / (number of moles of supplied acrolein) × 100 Yield (%) = (moles of acrylic acid produced) / (moles of acrolein fed) x 100 Selectivity (%) = (moles of acrylic acid produced) / (moles of acrolein reacted) x 100

[0037] The following examples are given with specific examples, but the present invention is not limited to these examples as long as they do not deviate from the gist of the present invention. The half-width of 2θ=22.2° shown in this example was obtained by analyzing data obtained by measuring the X-ray diffraction angle (2θ) using an UltimaIV manufactured by Rigaku Corporation under the conditions of X-ray CuKα radiation (λ=0.154 nm), output of 40 kV, 30 mA, measurement range of 5 to 60°, and measurement speed of 3° per minute, using OriginPro 2022b manufactured by LightStone. The analysis method was as described in the previous section, where a straight line passing through the minimum values ​​of 2θ=16.0°-18.0° and the minimum values ​​of 2θ=39.0°-42.0° in the X-ray diffraction pattern was used as the baseline, a quadratic function was fitted to the peaks above the baseline, and the half-width of the fitted quadratic function with an apex in the range of 2θ=22.2°±0.3° was read as the half-width of the peak at 2θ=22.2°±0.3° in the X-ray diffraction pattern.

[0038] [Example 1] <Production of Catalyst 1> Mo 12 The composition for V 2.7 W 0.8 Cu 1.5 Sb 0.50Ammonium molybdate, ammonium paratungstate, ammonium metavanadate, and antimony acetate were weighed and mixed in an aqueous solvent that was 5.2 times the mass of ammonium molybdate heated to 95 ° C., and then copper sulfate was added to obtain a preparation (A). This preparation (A) was dried by a spray drying method, and the resulting dried powder (B) was pre-fired at 350 ° C. for 4 hours to obtain a pre-fired body (C). The pre-fired body (C) was pulverized in a ball mill to obtain a pre-fired powder (E). 5% by mass of crystalline cellulose and 5% by mass of glass fibers with an average fiber length of 150 μm were added to the pre-fired powder (E), and after thorough mixing, the mixture was granulated by a rolling granulation method using a 20% by mass glycerin solution as a binder, and the mixture was shaped into a sphere on an inert spherical carrier consisting of a mixture of silica and alumina so that the loading rate was 33% by mass and the average particle size was 5 mm. A rolling granulator was used for molding, and the centrifugal acceleration was 26.0 G. Next, main calcination was carried out under conditions of 390° C. and 4 hours, to obtain a spherical catalyst 1 of the present invention.

[0039] [Example 2] <Production of catalyst 2> Mo 12 The composition for V 3.0 W 1.2 Cu 1.5 Sb 0.50Ammonium molybdate, ammonium paratungstate, ammonium metavanadate, and antimony acetate were weighed and mixed in an aqueous solvent that was 5.2 times the mass of ammonium molybdate heated to 95 ° C., and then copper sulfate was added to obtain a preparation (A). This preparation (A) was dried by a spray drying method, and the resulting dried powder (B) was pre-fired at 350 ° C. for 4 hours to obtain a pre-fired body (C). The pre-fired body (C) was pulverized in a ball mill to obtain a pre-fired powder (E). 5% by mass of crystalline cellulose and 5% by mass of glass fibers with an average fiber length of 150 μm were added to the pre-fired powder (E) and mixed thoroughly, and then the mixture was granulated by a rolling granulation method using a 20% by mass glycerin solution as a binder, and the mixture was shaped into a sphere on an inert spherical carrier consisting of a mixture of silica and alumina so that the loading rate was 33% by mass and the average particle size was 5 mm. A rolling granulator was used for molding, and the centrifugal acceleration was 26.0 G. Next, main calcination was carried out under conditions of 390° C. and 4 hours, to obtain a spherical catalyst 2 of the present invention.

[0040] [Example 3] <Production of catalyst 3> Mo 12 The composition for V 3.0 W 1.2 Cu 1.2 Sb 0.25 Ammonium molybdate, ammonium paratungstate, ammonium metavanadate, copper metal powder, and antimony acetate were weighed out so that the weight of the powder was 5.2 times that of the ammonium molybdate heated to 95°C, and mixed in an aqueous solvent, and then copper sulfate was added to obtain a mixed solution (A). The copper metal powder used was copper (powder) (standard: Grade 1, particle size: 75μm to 150μm) manufactured by Kanto Chemical Co., Ltd., and the amount used was 100g. 12The amount of Cu was adjusted so that the molar ratio of Cu to the total was 0.25, and the remaining amount of 0.95 was copper sulfate. This mixed solution (A) was dried by spray drying, and the resulting dried powder (B) was pre-calcined at 350°C for 4 hours to obtain a pre-calcined body (C). The resulting pre-calcined body (C) was pulverized in a ball mill to obtain a pre-calcined powder (E). 5% by mass of crystalline cellulose and 5% by mass of glass fiber with an average fiber length of 150 μm were added to the pre-calcined powder (E) and mixed thoroughly, and then the mixture was shaped into a spherical shape by rolling granulation using a 20% by mass glycerin solution as a binder on an inactive spherical carrier made of a mixture of silica and alumina so that the loading rate was 33% by mass and the average particle size was 5 mm. A rolling granulator was used for molding, and the centrifugal acceleration was 26.0 G. Next, the main calcination was performed at 390°C for 4 hours to obtain a spherical catalyst 3 of the present invention.

[0041] [Example 4] <Production of Catalyst 4> Mo 12 The composition for V 3.0 W 1.2 Cu 1.2 Sb 0.50 Ammonium molybdate, ammonium paratungstate, ammonium metavanadate, and antimony acetate were weighed and mixed in an aqueous solvent that was 5.2 times the mass of ammonium molybdate heated to 95 ° C., and then copper sulfate was added to obtain a preparation (A). This preparation (A) was dried by a spray drying method, and the resulting dried powder (B) was pre-fired at 350 ° C. for 4 hours to obtain a pre-fired body (C). The pre-fired body (C) was pulverized in a ball mill to obtain a pre-fired powder (E). 5% by mass of crystalline cellulose and 5% by mass of glass fibers with an average fiber length of 150 μm were added to the pre-fired powder (E), and after thorough mixing, the mixture was granulated by a rolling granulation method using a 20% by mass glycerin solution as a binder, and the mixture was shaped into a sphere on an inert spherical carrier consisting of a mixture of silica and alumina so that the loading rate was 33% by mass and the average particle size was 5 mm. A rolling granulator was used for molding, and the centrifugal acceleration was 26.0 G. Next, main calcination was carried out under conditions of 390° C. and 4 hours, to obtain a spherical catalyst 4 of the present invention.

[0042] [Comparative Example 1] <Production of Catalyst 5> Mo 12 The composition for V 3.0 W 1.2 Cu 1.2 The powders of ammonium molybdate, ammonium paratungstate, ammonium metavanadate, and metallic copper were weighed so that the mixture was 5.2 times the mass of the ammonium molybdate heated to 95°C, and then copper sulfate was added to obtain a mixed solution (A). The metallic copper powder was copper (powder) (standard: Grade 1, particle size: 75μm to 150μm) manufactured by Kanto Chemical Co., Ltd., and the amount used was such that the molar ratio of Cu to Mo12 was 0.50, and the remaining amount of 0.70 was copper sulfate. This mixed solution (A) was dried by a spray drying method, and the obtained dried powder (B) was pre-fired at 350°C for 4 hours to obtain a pre-fired body (C). The obtained pre-fired body (C) was pulverized in a ball mill to obtain a pre-fired powder (E). 5% by mass of crystalline cellulose and 5% by mass of glass fiber with an average fiber length of 150 μm were added to the pre-calcined powder (E) and mixed thoroughly, and then the mixture was shaped into a spherical shape by rolling granulation using a 20% by mass glycerin solution as a binder on an inactive spherical carrier made of a mixture of silica and alumina so that the loading rate was 33% by mass and the average particle size was 5 mm. A rolling granulator was used for molding, and the centrifugal acceleration was 26.0 G. Next, the main calcination was performed under conditions of 390 ° C. and 4 hours, to obtain a spherical catalyst 5 of the present invention.

[0043] [Comparative Example 2] <Production of Catalyst 6> Mo 12 The composition for V 3.0 W 1.2 Cu 1.2The powders of ammonium molybdate, ammonium paratungstate, ammonium metavanadate, and metallic molybdenum were weighed out and mixed in a water solvent that was 5.2 times the mass of the ammonium molybdate heated to 95°C, and then copper sulfate was added to obtain a mixture (A). The powder of metallic molybdenum was molybdenum (powder, 1-5 μm, ≧99.9% trace metals basis) manufactured by SIGMA-ALDRICH, and the amount used was such that, in terms of molar ratio, 0.50 of Mo12 was metallic molybdenum, and the remaining 11.5 was ammonium molybdate. This mixture (A) was dried by a spray drying method, and the resulting dried powder (B) was pre-fired at 350°C for 4 hours to obtain a pre-fired body (C). The resulting pre-fired body (C) was pulverized in a ball mill to obtain a pre-fired powder (E). 5% by mass of crystalline cellulose and 5% by mass of glass fiber with an average fiber length of 150 μm were added to the pre-calcined powder (E) and mixed thoroughly, and then the mixture was shaped into spheres by rolling granulation using a 20% by mass glycerin solution as a binder on an inactive spherical carrier made of a mixture of silica and alumina, so that the loading rate was 33% by mass and the average particle size was 5 mm. A rolling granulator was used for molding, and the centrifugal acceleration was 26.0 G. Next, the main calcination was performed under conditions of 390 ° C. and 4 hours, to obtain a spherical catalyst 6 of the present invention.

[0044] [Comparative Example 3] <Production of Catalyst 7> Mo 12 The composition for V 3.0 W 1.2 Cu 1.0 Sb 1.0Ammonium molybdate, ammonium paratungstate, ammonium metavanadate, and antimony acetate were weighed so that the weight of the mixture was 5.2 times that of the ammonium molybdate heated to 95 ° C., and then copper sulfate was added to obtain a mixture (A). This mixture (A) was dried by a spray drying method, and the resulting dried powder (B) was pre-fired at 350 ° C. for 4 hours to obtain a pre-fired body (C). The pre-fired body (C) was pulverized in a ball mill to obtain a pre-fired powder (E). 5% by mass of crystalline cellulose and 5% by mass of glass fibers with an average fiber length of 150 μm were added to the pre-fired powder (E), and after thorough mixing, the mixture was granulated by a rolling granulation method using a 20% by mass glycerin solution as a binder, and the mixture was shaped into a sphere on an inert spherical carrier consisting of a mixture of silica and alumina so that the loading rate was 33% by mass and the average particle size was 5 mm. A rolling granulator was used for molding, and the centrifugal acceleration was 26.0 G. Next, main calcination was carried out under conditions of 390° C. and 4 hours, to obtain spherical catalyst 7 of the present invention.

[0045] Oxidation reactions were carried out using the obtained catalysts 1 to 7. 67.6 ml of catalyst was packed into a reaction tube with an inner diameter of 28.4 mm, and a gas having the following composition, which was obtained by adding oxygen and nitrogen to the gas obtained by gas-phase catalytic oxidation of propylene using a molybdenum-bismuth catalyst, was introduced into the reaction tube, and the reaction was carried out at an SV (space velocity; flow rate of raw gas per unit time / apparent volume of packed catalyst) of 1020 / hr and a reaction bath temperature of 260°C. Acrolein 5.9vol% Unreacted propylene + other organic compounds 1.7 vol% Oxygen 4.7vol% Steam 17.2vol% Nitrogen-containing inert gas 70.5vol%

[0046] The reaction results obtained by the oxidation reaction are shown in Table 1, and the half-widths of the respective peaks in the X-ray diffraction patterns are shown in Tables 2 and 3. Table 3 is for reference only. [Table 1] [Table 2] [Table 3]

[0047] From the results in Tables 1 and 2, it was confirmed that the catalyst of the present invention has a high raw material conversion rate, that is, a high catalytic activity.

[0048] [Reference example 3] The catalyst described in Example 1 of Patent Document 1 was prepared according to the description in the Example of Patent Document 1. That is, ammonium tungstate, ammonium metavanadate, ammonium molybdate, antimony trioxide powder, and copper sulfate were used as raw materials, and Mo 12 The composition for V3W 1.2 Cu 1.2 Sb 0.5 A catalyst having a catalytically active component of the formula was obtained. When the half-width of the obtained catalyst was measured by the method described in the present invention, the half-width at 22.2°±0.3° in the X-ray diffraction pattern was 0.52. In addition, when an oxidation reaction was carried out by the method described in the present invention, the results were a reaction temperature of 260°C, a raw material conversion rate of 19.6%, a selectivity of 96.3%, and a yield of 18.9%.

[0049] This application is based on Japanese Patent Application No. 2023-150163, filed on September 15, 2023, the contents of which are incorporated herein by reference. [Industrial Applicability]

[0050] According to the present invention, when an unsaturated aldehyde is used as a raw material to produce an unsaturated carboxylic acid by a gas-phase catalytic oxidation reaction, the catalytic activity can be maintained at a high level. Therefore, the present invention is very useful because it prevents the thermal deterioration of the catalyst for producing acrylic acid and enables the plant to operate stably for a long period of time.

Claims

1. A catalyst for producing an unsaturated carboxylic acid, comprising a catalytically active component having a composition represented by the following formula (1), and an X-ray diffraction pattern obtained using CuKα radiation as an X-ray source has a half-width of a peak at 22.2°±0.3° of 0.65° or more and 1.35° or less: (Mo) 12 (V) a (W) b (1) c (Sb) d (X) e (Y) f (Z) g (O) h (1) (In formula (1), Mo, V, W, Cu, Sb, and O represent molybdenum, vanadium, tungsten, copper, antimony, and oxygen, respectively; X represents at least one element selected from the group consisting of alkali metals and thallium; Y represents at least one element selected from the group consisting of magnesium, calcium, strontium, barium, and zinc; Z represents at least one element selected from the group consisting of niobium, cerium, tin, chromium, manganese, iron, cobalt, samarium, germanium, titanium, and arsenic. Each of the elements represents at least one selected from the group consisting of a, b, c, d, e, f, g, and h. In addition, a, b, c, d, e, f, g, and h represent the atomic ratio of each element, and are 1.0≦a≦5.0, 0.50≦b≦3.0, 0.50≦c≦3.0, 0<d≦2.0, 0≦e≦0.50, 0≦f≦1.0, and 0≦g<6.0 relative to 12 molybdenum atoms. In addition, h represents the number of oxygen atoms required to satisfy the valence of each of the components.

2. 2. The catalyst for producing an unsaturated carboxylic acid according to claim 1, which is a catalyst in which a catalytically active component is supported on an inert carrier.

3. 3. The catalyst for producing an unsaturated carboxylic acid according to claim 2, wherein the inert support is silica, alumina or a combination thereof.

4. A method for producing an unsaturated carboxylic acid, using the catalyst for producing an unsaturated carboxylic acid according to claim 1.

5. A method for producing an unsaturated carboxylic acid, which uses a reaction tube packed with two or more types of the catalyst for producing an unsaturated carboxylic acid according to claim 1 in multiple layers.

Citation Information

Patent Citations

  • Catalyst and its production

    JP1996299797A

  • Catalyst for manufacturing acrylic acid

    JP2018043197A

  • Catalyst precursor, catalyst including the same, method for producing compound and method for producing catalyst

    JP2023080395A

  • Catalyst for acrylic acid production and process for producing acrylic acid using the catalyst

    WO2010038676A1

  • Catalyst for acrylic acid production, method for producing same, and method for producing acrylic acid

    WO2022050110A1